Echocardiographic findings in children with Tetralogy of Fallot - Shakya, Urmila; Sharma, Poonam; Shrestha, Manish (Nepalese Heart Journal, 2015)
Background and Aims: Tetralogy of Fallot (TOF) is the most common cyanotic congenital heart disease in children. The aim of this study was to identify various cardiac defects associated with TOF by transthoracic echocardiography.Methods: All children presenting to Shahid Gangalal National Heart Centre, with the diagnosis of TOF from 2014 to 2015 were included in the study. Echocardiograpic reports of all eighty eight children were reviewed.Results: The mean age of presentation was 3.5 } 3.9 years. Fifty six (64%) children were male and thirty two (36%) were female. Pulmonary artery anomaly was found in nine (10.2%) children which included hypoplastic pulmonary arteries, absent left pulmonary artery, post stenotic and aneurysmal dilatation of pulmonary artery. Pulmonary valve anomalies were seen in 13(14.8%) children which include pulmonary atresia, pin-hole opening of valve and bicuspid and absent pulmonary valve. Double outlet right ventricle, patent ductus arteriosus/major aortico-pulmonary collaterals, atrial septal defect and persistent left superior venacava were present in 12 (13.6%), 21 (23.9%), 22 (22.7%) and nine (10.2%) respectively. Right sided aortic arch was seen in 20 (22.7%).Conclusion: TOF is associated with various anatomical variations which need to be identified to avoid surgical complications. These can be diagnosed by echocardiography which has greatly reduced the need for invasive cardiac catheterization for these patients.Nepalese Heart Journal 2015;12(2):65-68